(untitled) (Journal of the College of Basic Education, 2025)
This research employs B and R filter observations to scrutinize and appraise the several Parameters attributes of star YY Eridani (Eri) at lower elevations. The data analysis unveils asymmetries and irregularities in the recorded light curves. The value of double star YY Eri lies in its ability to provide essential insights into the fundamental attributes of stars. Notably, binary stars are unique due to their distinct kinematic characteristics and chemical compositions.However, the recurring spectroscopic parallelism observed in the disk and the galactic corona are not entirely dissimilar. The numerical values of the parameters are tabulated for comparison with earlier studies. In this work, various physical parameters such as bolometric magnitudes, lifetimes, gravity darkening, Age, mass reflection coefficients, and empirical results of YY Eri are computed. The results align with those of previous studies